THE IMPORTANCE OF READING - Ataniyazova Sohiba Xamidovna (PEDAGOGS, 2025)
This article explores the importance of reading in the development of intellectual, emotional, and linguistic skills. It discusses how reading expands knowledge, strengthens language abilities, stimulates imagination, and reduces stress. The article also analyzes the long-term benefits of reading on personal growth and academic achievement. Emphasis is placed on the value of cultivating reading habits in both educational systems and daily life, considering reading as a foundational tool for lifelong learning and critical thinking.